Možnosti pridobivanja in uporabe gozdnega reprodukcijskega materiala navadnega koprivovca (Celtis australis L.) v Sloveniji - Jarni, Kristjan (Acta silvae et ligni, 2018)
Celtis australis (L.), the European Nettle Tree, is a tree typical of the Mediterranean and warmer sub Mediterranean forests, where it occurs individually or in small groups. The species is adapted to drought, it is resistant to diseases, pests and pollution and produces high quality wood. In order to promote and increase the proportion of Celtis australis in the forests, it should be artificially introduced for which, however, we do not have the appropriate forest reproductive material, neither the necessary experience with generative reproduction of the species. In the present study we analysed two stands of Celtis australis located near Brestovica and Opatje selo in the Karst region. The analysis showed that the size of both stands and good adaptation to local conditions supported the suitability to classify the stands as forest seed objects; a greater disadvantage is only the numerical lack of trees with excellent phenotypic properties. In favour of approval also speaks the fact that there are no better Celtis australis forest stands in Slovenia. In addition, the results of seed germination tests have shown that the generative reproduction of Celtis australis is relatively simple and that the best way is to sow seeds outdoor immediately after seed harvesting, i.e. in September, when the fruits are black-violet coloured. Relatively high germination of pre-stratified seeds is also achieved through sowing in spring.
Keywords: European nettle tree; forest reproductive material; germination; gozdni reprodukcijski material; kalitev; navadni koprivovec; seed; seed object; seme; semenski objekti